NON-UNIFORM INTERCONNECTEDNESS PATTERNS AND DYNAMICS: EVIDENCE FROM EMERGING STOCK MARKETS - Anca-Adriana SARAOLU (IONĂȘCUȚI) (Annals of the University of Oradea: Economic Science)
In the last decades, past financial crises have proved that financial markets worldwide are interconnected, however the subject was scarcely analysed from the viewpoint of financial stock markets. Therefore, the paper aims to analyse interconnectedness between emerging stock markets. The methodology employed is the “Wavelet Local Multiple Correlation” as it allowed to introduce the dominance feature and to capture the time-varying shifts in correlations, as well as the nonuniform frequencies over time. The study involves five emerging markets worldwide for a long-time span from 2005 to 2024. The results report considerable variations within the correlation pattern, at different frequencies over time. Therefore, the findings display considerable evidence of interconnectedness and temporal dependence among the emerging stock markets.